DIGITAL MARKETING MENTORING FOR THE MSME ELJOGJAWI_BATIKSANTRI VIA THE TIKTOK PLATFORM - Ahmad Hudaifah; Agustinus Tri Wicaksono; Arnoldus Yansen Kopong Samon; Naima Andleeb (SMARTINDO, 2025)
Digital marketing assistance for the MSME